2013
DOI: 10.1108/ijmce-03-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring frameworks: synthesis and critique

Abstract: Purpose -The purpose of this paper is to present a synthesis of the origins and theoretical frameworks of adult mentoring practices in educational and workplace settings along with an analysis and critique of their application to mentoring processes. Design/methodology/approach -The authors systematically analyzed books and articles published in peer-reviewed journals from 1978 to 2012 using qualitative meta-summary and qualitative meta-synthesis methodological approaches. Findings -This systematic review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 41 publications
0
68
0
Order By: Relevance
“…However, peer mentoring functions are not always well characterised in empirical studies which makes comprehensive evaluation of mentoring programmes challenging. It is suggested that peer mentoring could be more effective for both student and institutional outcomes when programmes are designed around the assessed mentoring needs of a target population (Dominguez and Hager, 2013).…”
Section: Straus and Marusic 2009)mentioning
confidence: 99%
“…However, peer mentoring functions are not always well characterised in empirical studies which makes comprehensive evaluation of mentoring programmes challenging. It is suggested that peer mentoring could be more effective for both student and institutional outcomes when programmes are designed around the assessed mentoring needs of a target population (Dominguez and Hager, 2013).…”
Section: Straus and Marusic 2009)mentioning
confidence: 99%
“…This form of mentoring relationship may be characterized as a deficit model in which mentors believe their role is to "help the mentee or coachee gain something from their knowledge or experience" (Salter, 2015, p. 77); others such as Dominguez and Hager (2013) prefer to view mentoring as a "developmental model". Dominguez and Hager (2013) and Parylo et al (2012), Searby (2014) stated that mentoring "should be viewed as a learning partnership between the mentor and the protégé" and that the vision of a passive mentee waiting for the mentor's wisdom is being challenged by a more active mentee stance. Thus, emphasis is placed on the importance of the roles of both mentors and mentees, contributing to the construction of an effective mentoring relationship.…”
Section: Definition Of Mentoringmentioning
confidence: 99%
“…According to Dawson (2014, p. 137) 'by 2007 there were more than 50 definitions of mentoring used in the research literature'. These definitions further multiply in the mentoring literature on mentoring frameworks (Dominguez and Hager, 2013), programmes (Kent et al, 2013) and models (Buell, 2004). Much of this literature focuses on the roles, procedures, functions and outcomes of mentoring.…”
Section: What We Did and Why We Did It Like Thismentioning
confidence: 99%